3,5,7-Substituted Pyrazolo[4,3- d]pyrimidine Inhibitors of Cyclin-Dependent Kinases and Their Evaluation in Lymphoma Models - Jorda, Radek; Havlíček, Libor; Šturc, Antonín; Maláriková, Diana; Daumová, Lenka; Alam, Mahmudul; Škerlová, Jana; Nekardová, Michaela; Peřina, Miroslav; Pospíšil, Tomáš; Široká, Jitka; Urbánek, Lubor; et al. (Journal of medicinal chemistry, 2019)
Cyclin-dependent kinases are therapeutic targets frequently deregulated in various cancers. By convenient alkylation of the 5-sulfanyl group, we synthesized 3-isopropyl-7-[4-(2-pyridyl)benzyl]amino-1(2) H-pyrazolo[4,3- d]pyrimidines with various substitutions at position 5 with potent antiproliferative activity in non-Hodgkin lymphoma cell lines. The most potent derivative 4.35 also displayed activities across more than 60 cancer cell lines. The kinase profiling confirmed high selectivity of 4.35 toward cyclin-dependent kinases (CDKs) 2, 5, and 9, and the cocrystal with CDK2/cyclin A2 revealed its binding in the active site. Cultured lymphoma cell lines treated with 4.35 showed dephosphorylation of CDK substrates, cleavage of PARP-1, downregulation of XIAP and MCL-1, and activation of caspases, which collectively confirmed ongoing apoptosis. Moreover, 4.35 demonstrated significant activity in various cell line xenograft and patient-derived xenograft mouse models in vivo both as a monotherapy and as a combination therapy with the BCL2-targeting venetoclax. These findings support further studies of combinatorial treatment based on CDK inhibitors.
Keywords: lymfom; pyrazoly; Bridged Bicyclo Compounds, Heterocyclic; bicyklické sloučeniny heterocyklické; Humans; inhibitory proteinkinas; pyrimidiny; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; Female; Drug Synergism; sulfonamidy; Antineoplastic Agents; Lymphoma; lidé; zvířata; proliferace buněk; myši; molekulární struktura; synergismus léků; apoptóza; Mice; Molecular Structure; xenogenní modely - testy protinádorové aktivity; Protein Kinase Inhibitors; ženské pohlaví; Cell Proliferation; nádorové buněčné linie; protinádorové látky; Xenograft Model Antitumor Assays; Animals; Cell Line, Tumor; Pyrimidines; Pyrazoles; Apoptosis; Sulfonamides